“Turning Their Back on Kids”: Inclusions, Exclusions, and the Contradictions of Schooling in Gentrifying Rural Communities - Jennifer Sherman; Kai A. Schafft (RSF: The Russell Sage Foundation Journal of the Social Sciences, 2022)
In this ethnographic case study of amenity-driven rural development, we illustrate how the school as a local institution can provide social, cultural, and educational privilege to some students while systematically withholding it from others. Rural gentrification, although representing new resources to historically struggling places, can exacerbate existing inequalities or create new ones, or both. This study not only challenges more communitarian visions of the rural school-community relationship, but also underscores the complexities and contradictions of rural development that can often inadvertently create, reproduce, or deepen social, cultural, and economic divides. These issues assume a particular saliency at a time of pronounced spatial, social, and economic division in the United States given that local institutions like public schools play vital roles in either bridging or widening these divides.